Book Review: Scelte Tecnologiche, Expertise e Aspetti Sociali della Produzione. Una Metodologia Multidisciplinare Applicata allo Studio della Ceramica Eneolitica by Vanessa Forte - Valeria Tiezzi (EXARC, 2021)
This book is a welcome addition to the bookshelf of Italian archaeologists interested in Prehistory and will certainly be of great use to those who are trying to gain a good understanding of pottery technology. Written in Italian, it is one of the few books in this language dealing with ceramic technology and the social aspects of the production by presenting, as a case study, the Copper Age domestic and funerary assemblages of the territory around Rome.